Real-time control of rotational servo system using Matlab Simulink and WinCon / Zakinah Yaakob - Yaakob, Zakinah (1998)
The objective of this project is to show that it is possible to use currently available commercial software, to model and simulate a Simulink Controller for a rotational servo system and running it in real-time. The software that involved in this project are Matlab Simulink, WinCon, Watcom C++ and Matlab Real-time Workshop. A model of a controller network is designed using state feedback controller and is compiled using Watcom C++ compiler. This compiler generates the real-time code using the Matlab Real-time Workshop and then linked to WinCon. WinCon is the real-time software component that runs the code generated from the Simulink Controller at specified sampling rate. The rotational servo system of this project consists of a DC Servo Motor with built-in gearbox whose ratio is 14 : 1. The objective of the controller is to control the position and velocity of the output shaft. The controller designed is based on pole placement method. The output response of this system can be obtained in real-time using WinCon.